The right skills for silver workers : an empirical analysis - (:unkn) unknown (Publications Office of the European Union, 2010)
"This research paper deals with skill mismatch among ageing workers. Not only is population ageing a dominant trend in the EU, but ageing workers are one of the groups particularly affected by skill mismatch. The paper features detailed empirical analyses of the impacts of skill mismatch on ageing workers and compares them with younger and prime-age workers. It discusses the determinants of different types of mismatch and provides a comprehensive analysis of its impacts on wages, job satisfaction, career and employment prospects and health. The results clearly indicate the need to take skill mismatch seriously and improve the use of skills in the workplace. It also highlights the role workplace conditions can play in better matching skills and jobs." (Hrsg., BIBB-Doku)
Keywords: G 1.1.1 Demografie; P 1.8 Ältere; G 1.2.3.2 Anforderungen & Bedarfe; G 2.3.1 Arbeitsteilung & -organisation; I 2.2 Europa; Demografischer Wandel; Älterer Arbeitnehmer; Qualifikationsanforderung; Arbeitsanforderungen; Mismatch; Einflussfaktor; Überqualifikation; Unterqualifikation; Überforderung; Unterforderung; Einkommen; Alter; Geschlecht; Arbeitszufriedenheit; Berufschance; Gesundheit; Empirische Untersuchung; Europa